EFFECT OF SOCIAL MEDIA ON CONSPICUOUS CONSUMPTION THROUGH BANDWAGON AND SNOB EFFECTS: A STRUCTURAL EQUATION MODELLING (Third Sector Social Economic Review, 2023)
Conspicuous consumption explains the way of consumption made by someone who want to influence others with the consumption activities they perform with the basic needs. Conspicuous consumption is a type of behavior that people buy the goods and services in order to show others their status and dignity. Social media, with the developing technology, is becoming a suitable environment for conspicuous consumption. The purpose of this study; to analyze the effect of social media on conspicuous consumption to reveal to what extent the snob and bandwagon factors have an intermediary effect between these variables. In research, data collected through the online survey method from 282 people who actively use social media. Analyzes of research data conducted using IBM SPSS Statistic 26 and IBM AMOS 23 package programs. As a result of two structural equation models conducted for the mediating effect of snob effect and bandwagon effect factors, a significant effect found between variables.
Keywords: Social Media; Conspicuous Consumption; Snob Effect; Bandwagon Effect; Structural Equation Model